Plastics end use applications - Rosato, Donald V. (SpringerBriefs in Materials, 2011)
Plastics End Use Applications is a SpringerBrief designed to keep professionals in the plastics industry abreast of key technical developments, business strategies and marketing initiatives in plastics and competitive materials that impact sales and usage. It is concisely focused on the five major competitive material areas?plastic, metal, paper and wood, rubber, and glass and ceramic?and how they interact in the twenty major plastic end-use market segments. For the global plastics professional, this book offers a way to enhance plastics technical and marketing insights. Plastics End Use Applications is of most value to manufacturing engineers, research and development professionals and general researchers interested in plastics and materials science.